Factors influencing youths’ attitude and relationships on religious appreciation : a case study in UiTM Kota Bharu / Muhammad Nur Izzan Abd Malek ...[et al.] - Abd Malek, Muhammad Nur Izzan; Mohd Muhaimin, Mursyidah; Othman, Nurul 'Aliyana (2020)
Islam is an official religion Malaysia and despite being an Islamic country, the number of youth involved in social problems such as drugs abuse, pre-marital sex which lead to the increasing rates of child abortion and even involving in terrorism in Malaysia. Although born and raised in Islamic education, they are still interested in getting involved in social problems. There are few aims of this study which is the first is to find the relationship and the direct effect of attitude towards religious appreciation. The second aims of this study is to find the significant and the direct effect of family, peers, education institutions and environment towards attitude. The last one is to study the significant and the direct effect of faith, worship and moral values towards religious appreciation. The total of 244 students from all five programmes in UiTM Kota Bharu are randomly selected to participate in this study. Questionnaires were used to collect data and the results were analyzed by using Structural Equation Model (SEM) analysis using AMOS. The findings of the research show that there is significant relationship between attitude (β= 0.516, p<0.001) and religious. The findings also show that there is significant relationship and direct effect of environment (β= 0.755, p<0.001), education (β= 0.925, p<0.001), family (β= 0.691, p<0.001) and peers (β= 1.000, p<0.001) towards attitude. The last findings show that there is significant relationship and direct effect of worship (β= 1.380, p<0.001), faith (β= 1.000, p<0.001) and moral values (β= 1.244, p<0.001) towards religious. Based on the findings, it can conclude that all the objective had achieved. The study recommend for the next study that to use the different factors or include some other news factor in order to get a new findings. Lastly, use the different sample such as juvenile school students for getting know whether there is a different findings if the samples is changed